Gender Negotiations and Patriarchal Culture: A Case Study of Career Women in the Village Community of Kembang Jeruk - Ihwan Amalih; Fitriani Fitriani (al-Afkar, Journal For Islamic Studies, 2026)
This research is motivated by the strong patriarchal cultural construction in rural communities, which influences the division of gender roles, particularly for women who carry out dual roles as career women. This study aims to analyze the forms of gender negotiation undertaken by career women and identify the strategies used to balance domestic and professional roles in Kembang Jeruk Village. The research used a qualitative approach with a case study method to gain an in-depth understanding of the phenomenon under study. The research subjects were purposively selected, namely career women living in Kembang Jeruk Village. Data collection techniques were conducted through in-depth interviews, participant observation, and documentation studies. The data obtained were analyzed using interactive analysis techniques that include data reduction, data presentation, and drawing conclusions, while maintaining validity through triangulation of sources and methods. The results indicate that gender negotiation undertaken by career women occurs in three main aspects: the division of domestic tasks, interpersonal relationships within the family, and participation in the public sphere. This negotiation process is carried out adaptively through patterns of compromise, open communication with partners, and consideration of prevailing cultural norms. This enables women to maintain their professional existence while gaining social legitimacy within their communities. Furthermore, career women employ various strategies to maintain role balance, including structured time management, flexible division of domestic duties, leveraging social support from family, choosing flexible work styles, and intensive communication within the family. Thus, this study concludes that a balance between domestic and professional roles for career women in a patriarchal cultural context can be achieved through adaptive gender negotiation supported by a conducive social environment.